PERANAN WANITA PENGOLAH IKAN ASIN DALAM MENINGKATKAN PENDAPATAN KELUARGA DI KELURAHAN BERBAS PANTAI KOTA BONTANG - Rina Indah Sari Tamrin; Erwiantono; Oon Darmansyah (Jurnal Pembangunan Perikanan dan Agribisnis, 2019)
The purpose of this study was to determine the income of fishermen families that involving wives in productive activities of salted fish processing and to know the role of fishermen's wives in the types of productive activities of salted fish processing and income contributions in increasing family income. This research was conducted in March 2018 - March 2019 in Berbas Pantai Village, Bontang City. The sampling method applied the census method that selected all of 15 fishermen households in research site, consisting of 15 husbands and 15 wives. The data obtained were analyzed using descriptive methods and to find out family income was analyzed using the analysis of revenue and income. The results of the family income analysis showed that women/wives who did processing by buying raw materials have smaller income ( average of Rp. 977,820.36 / month) than women/wives who did processing by obtaining raw materials through the husband's catch (average of Rp. 4,020,944.50 / month). The role of fishermen's wives in productive activities of salted fish processing were cleaning fish, drying and collecting the results of dried fish. The contribution of wives' income in the family was in average of 59% (for women who processed salted fish by buying the raw material) and 37% (for women who processed salted fish by obtaining raw material from the husband's catch).